Case Report: A Severe and Multi-Site Nocardia farcinica Infection Rapidly and Precisely Identified by Metagenomic Next-Generation Sequencing - Jiao, Mengfan; Deng, Xiang; Yang, Hongfu; Dong, Junqiang; Lv, Jun; Li, Fang (Frontiers in Medicine, 2021)
Nocardia genus is an aerobic, gram-positive, and opportunistic pathogen, which mainly affects cell-mediated immunosuppressed patients. Early diagnosis and treatment greatly improve prognosis. However, the limitation of golden standard-bacterial culture exists. Here, we report a 61-year-old male with pneumonia, sepsis and intermuscular abscesses induced by Nocardia farcinica. Venous blood culture reported negative results. Former improper diagnosis and treatment did not improve his condition. With the assistant of metagenomic next-generation sequencing, the pathogen was identified as Nocardia farcinica. He was then applied with accurate treatment and had a remarkable clinical and radiological improvement.